A de novo Stereocontrolled Synthetic Approach to a Functionalized Indolizidine Core - Nonn, Melinda; Escorihuela, Jorge; Kiss, Loránd (Synlett, 2022)
A convenient domino synthetic approach for the construction of the indolizidine core in diastereoselective manner has been developed from inexpensive starting compounds, providing triple functionalization. The novel synthetic route started from β-lactam derived from 1,5-cyclooctadiene including a ring-opening metathesis/cross-metathesis sequence as key steps with methyl acrylate followed by intramolecular ring closure across an aza-Michael addition. The process gave functionalized indolizidine framework with stereocontrol in high yields. DFT calculations supported the experimentally observed stereoselective reaction.
Keywords: azaheterocycles; indolizidine; metathesis; ring closure; stereocontrol